THE RELATIONSHIP BETWEEN BEHAVIOR OF PARENT, DISCIPLINE, AND INTEREST IN LEARNING TOWARD LEARNING OUTCOME OF MATHEMATICS OF STUDENT ON SMP N 5 BANGUNTAPAN - Rima Nur’Afifah; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Low student learning outcomes associated with many factories. The behavior of parent, discipline, and interest in learning are some of the factors associated with learning outcomes. The aim of this study to know there or not the relationship that positive and significant between the behavior of the parent, discipline, and interest in learning by mathematics learning outcomes of student class VII the state junior high school 5 Banguntapan Regency Bantul semester even at academic year 2015/2016. The Population in this research is all of students class VII that aggregate 4 classes. The sample taken from class VII D a class of research samples with a random sampling technic toward class. The aggregation data technic is doing with the questionnaire and test method. Test of research instrument: validity test, reliability test and power of different tests. Analysis prerequisite test includes a normality test, linearity test, and independent tests. Analysis of the data is using product correlation moment analysis and multiple linear regression analysis. The result shows that there a positive and significant relation between: 1) behavior of parent by learning result of mathematics, with  Ŷ= -16,5147 + 0,6029X1; 2) discipline by learning result of mathematics, with  Ŷ= -23,4033 + 0,6410X2; 3) interest in learning by learning result of mathematics, with  Ŷ= 8,5553 + 0,4107X3 ; 4) behavior of parent and discipline by learning result of mathematics, with   Ŷ= -32,8843 + 0,2669X1+0,4879X2  as well as SR  X1=30,0072% and SR  X2= 69,9927%; 5) behavior of parent and interest in learning by learning result of mathematics, with  Ŷ= -29,6738 + 0,4842X1+0,2945X3 along with SR  X1=58,9627% and SR X3= 41,0373%;  6) discipline and interest in learning by learning result of mathematics, with  Ŷ= -33,3746+0,5354X2+0,2475X3 along with SR  X2= 70,6966% and SR X3= 29,3034%;  7) behavior of parent, discipline and interest in learning by learning result of mathematics, with  Ŷ= -41,5944 + 0,2252X1 + 0,4134X2 + 0,2306X3 with SR  X1= 22,1532%, SR  X2= 51,891% and SR X3 = 25,9558%.